Tertiary Lymphatic Structures in Primary Hepatic Carcinoma: Controversy Cannot Overshadow Hope - Jia, Weili; Zhang, Tianchen; Yao, Qianyun; Li, Jianhui; Nie, Ye; Lei, Xinjun; Mao, Zhenzhen; Wang, Yanfang; Shi, Wen; Song, Wenjie (Frontiers in Immunology, 2022)
The incidence of primary hepatic carcinoma (PHC), a highly lethal disease, has continued to increase in recent years. Tertiary Lymphoid Structures (TLS) are being paid attention by many researchers because of their unique influence on the progress of PHC. In this paper, we review the studies referred to TLS in PHC in late years and briefly introduce the background concept of TLS. The dual impact of TLS distribution in PHC on prognosis and the potential of TLS-related components for PHC treatment are highlighted with the aim of providing a reference for future studies.